The Effects of Pre-Pregnancy Body Mass Index and Weight Gain During Pregnancy on Perinatal Outcomes: A Retrospective Cohort Study - Engin Yurtcu; Sibel Mutlu; Enis Ozkaya (Gynecology Obstetrics & Reproductive Medicine)
OBJECTIVE: To investigate the effects of pre-pregnancy body mass index and weight gain during pregnancy on perinatal outcomes and delivery mode.